Life : it is your choice? - Tan, Jie Lin (2019)
Social norms serve as implicit guides to our way of living - especially so in Singapore. Over decades, the pro-family policies of Singapore and its sociocultural climate - in the name of economic development and “Asian values” - have inevitably paved a singular, expected life trajectory for its citizens: have a ‘good’ education, a ‘good’ job, a ‘happy’ marriage, ‘accomplished’ children and a ‘comfortable’ retirement. Monetary incentives and benefits are given by the government to encourage certain ways of life, but inevitably ends up reinforcing this single narrative. Many Singaporeans consciously or unconsciously make their life choices in order to receive these benefits to get ahead in life. This single story is what is defined to be the ‘normal’ Singaporean life. When we are convinced that such norms are the only path acceptable and ideal, it excludes all others who wish not, or simply cannot fit into this single story, by the differences of class, gender, sexuality, race, etc. We Singaporeans tend to believe it is all up to the individual to make their life choices, and the failure to live up to the single story becomes a responsibility of the individual and individual family units - despite the strong social expectations and structural factors. This project is a metaphor of Singapore’s norms - in five categories it deconstructs structural factors – especially government’s social policies and benefit schemes, to ask the question: Life: who’s choice is it? Is it your choice?